Association of Catharanthus yellow mosaic virus and a novel Tomato leaf curl Lucknow betasatellite with papaya leaf curl disease (PaLCD) in India - Priyanka; Yusuf Akhter; Sangeeta Saxena (The Microbe)
Papaya leaf curl disease (PaLCD) poses a significant threat to global papaya production, driven by complex infections involving various begomovirus-betasatellite combinations. These infections complicate resistance breeding and disease management strategies due to the continuous emergence and geographical spread of novel viral strains. In this study, we investigated papaya plants with severe leaf curl disease symptoms in the Lucknow region of U.P, India. Molecular characterization revealed the presence of a begomovirus and associated satellite molecules. Analysis of the full-length DNA-A component of one begomovirus isolate (PP998006) showed a 93 % nucleotide similarity with Catharanthus yellow mosaic virus (CaYMV). The associated betasatellite sequence (PP998007) exhibited 90.5 % nucleotide identity with the Tomato leaf curl betasatellite-Pune isolate (ToLCB). Based on the species demarcation threshold for betasatellites (identity >91 %), we proposed this novel betasatellite as Tomato leaf curl Lucknow betasatellite (ToLCLB). In addition, a deltasatellite sequence (PP998008) was identified, with 98.3 % nucleotide identity to Papaya leaf curl distortion deltasatellite 1 (PaLCDD). This study represents the first report of co-infection in papaya plants in Lucknow by CaYMV, ToLCLB, and PaLCDD. It is also the first documentation of CaYMV infecting papaya in India. These findings reveal the complexity of PaLCD in this region, characterized by novel viral combinations, and emphasize the urgent need for further research into viral diversity, host interactions, and integrated management strategies to mitigate the disease impact.